Polytropic Influence of TRIB3 rs2295490 Genetic Polymorphism on Response to Antihypertensive Agents in Patients With Essential Hypertension - Zhou, Jiecan; He, Fazhong; Sun, Bao; Liu, Rong; Gao, Yongchao; Ren, Huan; Shu, Yan; Chen, Xiaoping; Liu, Zhaoqian; Zhou, Honghao; Deng, Sheng; Xu, Heng; et al. (Frontiers in Pharmacology, 2019)
Tribbles homolog 3 (TRIB3) mediating signaling pathways are closely related to blood pressure regulation. Our previous findings suggested a greater benefit on vascular outcomes in patients carrying TRIB3 (251, A>G, rs2295490) G allele with good glucose and blood pressure control. And TRIB3 (rs2295490) AG/GG genotypes were found to reduce primary vascular events in patients who received the intensive glucose treatment as compared to those receiving the standard glucose treatment in type 2 diabetic patients. However, the effect of TRIB3 genetic variation on antihypertensives was not clear in essential hypertension patients. A total of 368 patients treated with conventional dosage antihypertensives (6 groups, grouped by atenolol/bisoprolol, celiprolol, doxazosin, azelnidipine/nitrendipine, imidapril, candesartan/irbesartan) were enrolled in our study. Genetic variations were successfully identified by sanger sequencing. A linear mixed model analysis was performed in blood pressure among TRIB3 (251, A>G) genotypes and adjusted for baseline age, gender, body mass index, systolic blood pressure (SBP), diastolic blood pressure (DBP), total cholesterol and other biochemical factors appropriately. Our data suggested that TRIB3 (251, A>G) AA genotype carriers showed better antihypertensive effect than the AG/GG genotype patients (P=0.014 for DBP and P=0.042 for mean arterial pressure (MAP)), with a maximal reduction of DBP by 4.2 mmHg and MAP by 3.56 mmHg after azelnidipine or nitrendipine treatment at 4th week. Similar tendency of DBP-change and MAP-change was found for imidapril (ACEI) treatment, in which marginally significances were achieved (P=0.073 and 0.075, respectively). Against that, we found that TRIB3 (251, A>G) AG/GG genotype carriers are beneficial for antihypertensive therapy of ARBs with a larger DBP-change during the period of observation (P=0.036). Additionally, using the stratified analysis, we found that the difference in antihypertensive effect would be more obvious (the maximal blood pressure change was 13 mmHg for the MAP between male and female patients with AA genotype who taken ARBs). In conclusion, our data supported that TRIB3(251, A>G) genetic polymorphism may serve as a useful biomarker in determining the prescription for certain antihypertensive drugs.